COMMUNITY PERCEPTIONS AND ADAPTATION STRATEGIES TO RECURRENT FLOODING: A CASE STUDY OF LOCAL COMMUNITIES IN NAGARI PELANGAI, RANAH PESISIR SUB-DISTRICT, PESISIR SELATAN DISTRICT - Sinaga, Enjelina C; Rahmi, Ulva; Anarku, Faras Fazira; Madrisah, Elsi; Aisyah, Nurul; Atfiano, Tio (Remote Sensing Technology Study Program, 2025)
Nagari Pelangai, located in Pesisir Selatan Regency, is one of the coastal areas that experiences recurrent flooding every year. This research aims to analyze the community's views on flood disasters that occur on an ongoing basis and explore the adaptation strategies they apply before and after flooding. The method used in this research is a descriptive qualitative approach with a phenomenological approach, which involves in-depth interview techniques, field observations, and documentation collection. The results show that the community has various views on flooding: some consider it a normal natural phenomenon, some see it as a worrying threat, and some view it as an event that needs to be watched out for. The adaptation strategies implemented include preventive measures such as building houses with more height, storing important items in a safe place, as well as responsive measures such as self-evacuation and cleaning up after flooding. However, most adaptation efforts are still individual and not collectively coordinated. These findings point to the importance of structural support and community capacity building in developing sustainable and locally-based adaptation strategies